2015
DOI: 10.1016/j.cmi.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the hajj on pneumococcal transmission

Abstract: Over two million Muslim pilgrims assemble annually in Mecca and Medina, Saudi Arabia, to complete the Hajj. The large number of people in a crowded environment increases the potential for pneumococcal carriage amplification. We evaluated pneumococcal carriage prevalence with four cross-sectional studies conducted at beginning-Hajj (Mecca) and end-Hajj (Mina) during 2011 and 2012. A questionnaire was administered and a nasopharyngeal swab was collected. The swab was tested for pneumococcus, serotype and antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 30 publications
(43 reference statements)
9
55
1
Order By: Relevance
“…Pilgrims acquired antibiotic non-susceptible Streptococcus pneumoniae at a rate of 6.1% compared with 2.5% pretravel and had increased acquisition of multiple drug-resistant S. pneumoniae from 0.6% to 2.2% [21]. It has been reported that as many as one-third of pilgrims acquire S. pneumoniae during the Hajj [22].…”
Section: Role Of Pilgrims In the Dissemination Of Antibiotic Resistancementioning
confidence: 98%
“…Pilgrims acquired antibiotic non-susceptible Streptococcus pneumoniae at a rate of 6.1% compared with 2.5% pretravel and had increased acquisition of multiple drug-resistant S. pneumoniae from 0.6% to 2.2% [21]. It has been reported that as many as one-third of pilgrims acquire S. pneumoniae during the Hajj [22].…”
Section: Role Of Pilgrims In the Dissemination Of Antibiotic Resistancementioning
confidence: 98%
“…Performing Hajj rituals is a risk factor for pneumococcal acquisition [2,14]. There is currently limited microbiological data regarding the prevalence and causes of respiratory infection during Hajj.…”
Section: Discussionmentioning
confidence: 99%
“…Overcrowding situations was a risk factor for transmission of infections especially for organisms that were transmitted via airborne and droplets. Streptococcus pneumoniae was among the most common organism isolated from respiratory tract among hajj pilgrims with respiratory tract infections [2]. In a recent study, almost 20% of pilgrims had acquired S. pneumoniae nasal colonization post hajj [3].…”
Section: Introductionmentioning
confidence: 99%
“…This challenge is not only for Saudi Arabia but also internationally with the risk of pilgrims importing infectious diseases into their home countries when they return [2]. Respiratory tract infections, including influenza and pneumonia, are the leading health risks at Hajj [3][4][5][6]. Emerging infections like Middle East respiratory syndrome coronavirus (MERS-CoV) pose additional threats to disease control [7,8].…”
Section: Introductionmentioning
confidence: 99%